SOSIALISASI DAN BANTUAN MESIN PELET UNTUK PENINGKATAN PRODUKTIVITAS TERNAK SAPI DI KABUPATEN BONE - Djamaluddin, Fauzan; Renreng, Ilyas (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2025)
Cattle farmers in Bone Regency usually lack stock of cattle feed in the form of grass and straw during the dry season. Usually grass or straw is not stored in the warehouse due to limited space. The supply of cattle feed is adjusted when daily needs are not based on each month or year. Cattle farmers in Bone Regency still carry out the process of transporting grass or straw naturally so that the capacity of the feed transported is small and takes a long time. To obtain 5-10 kg of cattle feed, it takes a day while the cattle need is 60-120 kg per day. To increase the productivity of farmers in the fattening process, cattle feed pellet machine technology is needed. Therefore, through the program to the community of UNHAS - community partnership program (PPMU-PKM) we propose cattle feed pellet machine technology to increase the productivity of cattle farmers in Bone Regency.